Sports Injury Patterns and Incidence Among Adolescent Pencak Silat Athletes - Pambudi, Yudhi Teguh; Widorotama, Angger; Yunika, Novia; Hasan, Muhamad Fahmi; Ilsya , Marisa Noviyanti Fajrah; Hartianto, Naufal Dzaki (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2025)
The expanding popularity of Pencak Silat, particularly in the full-contact sparring category, exposes athletes to significant injury risks caused by intrinsic and extrinsic factors, including the implementation of complex new regulations. Therefore, a comprehensive understanding of these rules by referees is critical to mitigate injuries and prioritize athlete safety. This study aims to analyze the incidence of injuries among pencak silat athletes participating in the Pekan Olahraga Pelajar Daerah, a regional multi-event Regional Student Sports Week in Indonesia at the district level in the regencies of Banyumas, Cilacap, Purbalingga, and Banjarnegara, Central Java Province. This study employed a cross-sectional survey design, involving 142 adolescent pencak silat athletes selected through purposive sampling. Data were collected using a structured questionnaire adapted from Fuller et al and supplemented by interviews to validate responses. The questionnaire focused on athlete demographics, injury characteristics, and affected body regions. Data were analyzed using descriptive statistics, including frequency distribution and percentage calculations, to provide an empirical overview of injury patterns and incidence rates. The majority of injuries occurred during training sessions (87%) rather than competitions (27%). Chronic injuries were more prevalent (85%) compared to acute injuries (15%). The lower extremities were the most affected body parts (77%), particularly the knee (26%), ankle (24%), and hip (24%). Pencak silat athletes are more prone to chronic injuries, particularly in the lower extremities. Injury prevention efforts should focus on proper warm-up routines, injury education, and enhancing technical skills to minimize injury risks during both training and competition. Keywords: pencak silat, sports injuries, injury assessment, injury prevention.